Theoretical Analysis of Thermodynamic Effect of Cavitation in Cryogenic Inducer Using Singularity Method - S. Watanabe; A. Furukawa; Y. Yoshida (International Journal of Rotating Machinery)
Vapor production in cavitation extracts the latent heat of evaporation from the surrounding liquid, which decreases the local temperature, and hence the local vapor pressure in the vicinity of cavity. This is called thermodynamic/thermal effect of cavitation and leads to the good suction performance of cryogenic turbopumps. We have already established the simple analysis of partially cavitating flow with the thermodynamic effect, where the latent heat extraction and the heat transfer between the cavity and the ambient fluid are taken into account. In the present study, we carry out the analysis for cavitating inducer and compare it with the experimental data available from literatures using Freon R-114 and liquid nitrogen. It is found that the present analysis can simulate fairly well the thermodynamic effect of cavitation and some modification of the analysis considering the real fluid properties, that is, saturation characteristic, is favorable for more qualitative agreement.